Enhanced durability predicts success in amateur road cycling: evidence of power output declines - Barsumyan, A.; Soost, C.; Burchard, R. (Frontiers in Sports and Active Living, 2025)
Purpose: Durability refers to an athlete's capacity to sustain optimal performance levels during prolonged physical exertion. Durability has been recognized as important and remains a key factor in endurance performance, particularly among amateur athletes who make up the largest segment of the endurance sports community. In the modern era, where remote coaching has become increasingly prevalent, there is a need for new methods to measure durability effectively without the constraints of laboratory. The aim of this study was to quantify durability in well-trained age-group cycling athletes using home-based test measures, identify durability as an important predictor of endurance performance, and provide practical recommendations for improving durability through training.